A facile preparation of pH‐temperature dual stimuli‐responsive supramolecular hydrogel and its controllable drug release. Issue 15 (24th December 2015) - Zhou, Mi; Liu, Kaiyue; Qian, Xin
ABSTRACT: A series of pH‐temperature dual stimuli‐responsive random copolymers poly[ N, N ‐dimethylaminoethyl methacrylate‐ co ‐poly(poly(ethylene glycol) methyl ether methacrylate][poly(DMAEMA‐ co ‐MPEGMA)] were synthesized by free radical polymerization. The supramolecular hydrogel was formed by pseudopolyrotaxane, which was prepared with the host‐guest interactions between α‐cyclodextrin (α‐CD) and poly(ethylene glycol) (PEG) side chains. Fourier transform infrared (FT‐IR), nuclear magnetic resonance ( 1 H NMR), and X‐ray diffraction (XRD) confirmed the structures of the hydrogels. The pH‐temperature dual stimuli responsive properties of the hydrogels were characterized by rheometer. Finally, the controllable drug release behavior of the hydrogel, which was used 5‐fluorouracil (5‐Fu) as the model drug, was investigated at different temperatures and different pH values. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43279. Abstract :